Analysis of the impact of some monetary and fiscal policy variables on inflation and unemployment in the Iraqi economy for the period (2005-2022) - Ali, Hayder Hussein; Razzaq, Kawthar Kareem Abdul; Abbood, Ali Al-Hadi Rashid (Journal of Posthumanism, 2025)
The research deals with measuring and analyzing how the fiscal and monetary is related to inflation and rates of unemployment in the economy in Iraq between 2005-2022, and this topic has been addressed to find out the role played by these two policies in achieving economic stability. This can happen when inflation and unemployment rates are controlled, the research started from the premise that there is no economic balance between macroeconomic variables, and the separation of the behavior of the financial and monetary policies from some real macro variables such as inflation and unemployment, and for proving the hypothesis was used. The study has found that there is a discrepancy in the variables of the Qiddiya and financial policies and the coordination lack between the two policies in affecting inflation and unemployment rates, and this approves the research hypothesis, and the research recommends working to adopt financial policies generating investments driving the economic wheel by developing new plans for investment spending in the real sector by the movement of high-productivity activities the external sector is not able to compete with by the open-door policy, which It works to attract the labor force and eliminate unemployment. All the tables are created by the (12EViews.) by the researchers.